2020
DOI: 10.1055/s-0040-1709736
|View full text |Cite
|
Sign up to set email alerts
|

Escoliose degenerativa do adulto

Abstract: ResumoO envelhecimento da população aumenta a incidência dos processos degenerativos osteomusculares, como a escoliose do adulto (EA). A EA é definida como uma deformidade da coluna no plano coronal com ângulo de Cobb > 10° e pode ocorrer devido a um processo degenerativo (escoliose de novo), evolução de uma escoliose pré-existente ou de forma iatrogênica.A EA é uma doença potencialmente limitante que acomete um grupo heterogêneo de pacientes. O tratamento clínico se mostrou pouco efetivo e a indicação cirú… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 33 publications
0
2
0
Order By: Relevance
“…The prevalence of ASD increases with age, reaching 32%-68% in people aged 65 years or over. 1,2 Spinal curvature progresses at 18-68 per year, 3 resulting in impaired lung function, reduced daily activity, and increased mortality. 4 Since pain is often only partially relieved by postural compensation and patients are unable to self-manage, ASD often progresses to a point where surgical treatment is necessary.…”
Section: Introductionmentioning
confidence: 99%
“…The prevalence of ASD increases with age, reaching 32%-68% in people aged 65 years or over. 1,2 Spinal curvature progresses at 18-68 per year, 3 resulting in impaired lung function, reduced daily activity, and increased mortality. 4 Since pain is often only partially relieved by postural compensation and patients are unable to self-manage, ASD often progresses to a point where surgical treatment is necessary.…”
Section: Introductionmentioning
confidence: 99%
“…The intervertebral disc (IVD) consists of a soft central nucleus pulposus, a tough annulus fibrosus, and a hyaline cartilage endplate, which acts as a shock absorber in the spine and allows for spinal motion. Studies have demonstrated that with aging, changes such as an increase in protease activity and a decrease in proteoglycan synthesis led to a reduction in the height and mechanical properties of the IVD, which contributed to the onset and development of ADS [ 7 ]. In turn, ADS can further aggravate IVDD [ 8 ], which forms a vicious circle.…”
Section: Introductionmentioning
confidence: 99%